2021
DOI: 10.1002/ana.26186
|View full text |Cite
|
Sign up to set email alerts
|

DNase Treatment Prevents Cerebrospinal Fluid Block in Early Experimental Pneumococcal Meningitis

Abstract: Objective: Streptococcus pneumoniae is the most common cause of bacterial meningitis, a disease that, despite treatment with antibiotics, still is associated with high mortality and morbidity worldwide. Diffuse brain swelling is a leading cause of morbidity in S pneumoniae meningitis. We hypothesized that neutrophil extracellular traps (NETs) disrupt cerebrospinal fluid (CSF) transport by the glymphatic system and contribute to edema formation in S pneumoniae meningitis. Methods: We used DNase I treatment to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 52 publications
(114 reference statements)
4
10
0
Order By: Relevance
“…On the other hand, Pavan and collaborators have recently observed that upon neuroinflammation caused by a pneumococcal infection in the CNS, AQP4 expression levels are not significantly altered compared to a non-infected situation. Our results go in line with Pavan et al [29], as we did not observe increased AQP4 expression levels in the brains from the meningitis-affected rats compared to the brains from the sham control mice. Significantly, what affects the solute transport of the glymphatic system during pneumococcal meningitis is not the altered AQP4 expression, but rather the disruption of the AQP4-water channels due to a detachment of the astrocytic end feet from the BBB vascular endothelium.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…On the other hand, Pavan and collaborators have recently observed that upon neuroinflammation caused by a pneumococcal infection in the CNS, AQP4 expression levels are not significantly altered compared to a non-infected situation. Our results go in line with Pavan et al [29], as we did not observe increased AQP4 expression levels in the brains from the meningitis-affected rats compared to the brains from the sham control mice. Significantly, what affects the solute transport of the glymphatic system during pneumococcal meningitis is not the altered AQP4 expression, but rather the disruption of the AQP4-water channels due to a detachment of the astrocytic end feet from the BBB vascular endothelium.…”
Section: Discussionsupporting
confidence: 93%
“…AQP4 is a water channel present on the end feet of perivascular astrocytes, which are in contact with the vascular endothelium of the BBB, and AQP4-water channels regulate the solute transport of the glymphatic system [26][27][28]. It was recently reported that AQP4 levels are not altered in the brain cerebral cortex during pneumococcal meningitis [29]. In line with these recent findings, our western blot analysis using brain homogenates clearly showed that upon experimental pneumococcal meningitis, AQP4 protein levels are not altered comparing brain tissue of the rats from sham and meningitis groups over time (Figures 8A and 8B).…”
Section: Loss Of Astrocytic Interaction With the Bbb Vascular Endothe...mentioning
confidence: 99%
“…Intracisternal administration of pneumococci in the CSF progressively caused decreased drainage of CSF into the brain parenchyma and diminished fluid return into the peripheral circulation. This finding is in line with a study by Pavan and collaborators in which it was reported that pneumococcal meningitis induced with intracisternal administration of S. pneumoniae caused accumulation of a fluorescent tracer in the CSF compartment as a consequence of impaired functionality of the glymphatic system ( 11 ). In this study, we newly observed a significant accumulation of pneumolysin and pneumococcal capsule localized in the CSF compartments rather than in the brain parenchyma over time.…”
Section: Introductionsupporting
confidence: 91%
“…By using a rat model, it was demonstrated that NET‐formation disrupt cerebrospinal fluid transport. This may elicit oedema in the CNS infected with Streptococcus pneumonia , the most common cause of bacterial meningitis, and thereby exacerbate the disease 20 . This unexpected consequence of NET formation may be considered as a serious collateral damage induced by the NETS.…”
Section: Introductionmentioning
confidence: 99%
“…This may elicit oedema in the CNS infected with Streptococcus pneumonia , the most common cause of bacterial meningitis, and thereby exacerbate the disease. 20 This unexpected consequence of NET formation may be considered as a serious collateral damage induced by the NETS. DNase treatment disrupting NETs re‐established the fluid transport and thereby prevented brain oedema and weight increase.…”
Section: Introductionmentioning
confidence: 99%